Clostridium difficile-mediated effects on human intestinal epithelia: Modelling host-pathogen interactions in a vertical diffusion chamber. (February 2016) - Jafari, Nazila V.; Kuehne, Sarah A.; Minton, Nigel P.; Allan, Elaine; Bajaj-Elliott, Mona
Abstract: Clostridium difficile infection is one of the leading causes of healthcare associated diarrhoea in the developed world. Although the contribution of C. difficile toxins to disease pathogenesis is now well understood, many facets of host-pathogen interactions between the human intestinal epithelia and the C. difficile bacterium that may contribute to asymptomatic carriage and/or clinical disease remain less clear. Herein, we tested the hypothesis that C. difficile strains mediate intestinal epithelial cell (IEC) antimicrobial immunity via toxin dependent and independent means and that the 'anaerobic' environment has a significant impact on bacterial-IEC interactions. Crosstalk between three C. difficile PCR ribotypes (RT) [RT027 (strain R20291), RT012 (strain 630) and RT017 (strains M68 and CF5)] and IEC cell-lines were investigated. All RTs showed significant engagement with human Toll-like receptors (TLR)-5, TLR2-CD14 and TLR2/6 as measured by IL-8 release from TLR-transfected HEK cells. Co-culture studies indicated minimal impact of R20291 and 630 TcdA and TcdB on bacterial adherence to Caco-2 cells. An apical anaerobic environment had a major effect on C. difficile -T84 crosstalk as significantly greater cytokine immunity and trans-epithelial electrical resistance (TEER) dysfunction was recorded when co-cultures were performed in an Ussing chamber system compared to standard 5% CO2 conditions. Overall, this study suggests that anaerobic C. difficile engagement with human IECs is a complex interplay that involves bacterial and toxin-mediated cellular events. Highlights: Characterization of bacterial adherence to intestinal epithelial cell-lines. Specific TLRs activation in response to Clostridium difficile RT027 and RT012 strains. C. difficile -mediated effect on host innate immune response(s) in anaerobic condition. C. difficile -mediated effects on host intestinal epithelial barrier function.